Plan de mejoramiento empresarial para la implantación de las técnicas de mejora continúa a la empresa LESGO S.A.S en la ciudad de Cali (2017)
According to the mission of the Business Administration program, it was proposed this preliminary draft, which is based on the investigation of factors thatleading to the improvement of the processes of the company LESGO S.A.S, this social object production and marketing of plastic shoes in the city of Cali, Valle del Cauca, the need to organize the processes and give addressing, strategies to the company are the main problems that the company has, despite this, has a large investment of capital, of machinery and equipment, has not given the profitability and profit that should lack adequate strategic direction that leads to acquire competitive advantages and differentiate it from other competitors. The first part of the work is the theme, which is an improvement plan for the implementation of the techniques of continuous improvement to the company LESGO S.A.S in the city of CALI, VALLE, the presentation of the subject and the characteristics of the company and a small historical review.